Effectiveness of Erythropoietin on Working Memory, Passive Avoidance Learning and Anxiety- Like Behaviors in Prenatal Food Restriction Model - Neda Bagha; Mohammad Amin Edalatmanesh (Islamic Azad University, 2018)
Introduction: Prenatal Food Restriction (PFR) causes some disorders in prenatal development and neuro-developmental abnormalities. On the other hand, the studies indicated that erythropoietin can act as a neuro-protector. Therefore, the aim of this study is to analyze the effects of erythropoietin on working memory, passive avoidance learning, and anxiety level in rat PFR model. Methods: In this experimental study, 50 neonatal rats are exposed to PFR. Reduction of standard food portion up to 50% has been started on the embryonic day (ED) 14 in rats until postnatal period. Then, different doses of 500, 1000, and 2000 IU/kg weight erythropoietin were injected to experimental groups, subcutaneously. At post natal day (PND) 30; Y-maze, shuttle box and elevated plus maze (EPM) are used for evaluation of working memory, passive avoidance learning, and anxiety level, respectively. Differences between groups were analyzed by one way ANOVA with Tukey's post hoc (p ˂ 0.05). Results: The results indicate that working memory and avoidance learning have reduced significantly in the control group (p ˂ 0.05). Moreover, anxiety level has increased in PFR group in comparison with the control group (p ˂ 0.001). On the other hand, working and avoidance memories have increased in those groups which received EPO in comparison with PFR groups and anxiety level have decreased significantly (p ˂ 0.05). Conclusion: Our results indicate that prenatal treatment of erythropoietin can ameliorate behavioral abnormalities in PFR model.